2002
DOI: 10.1093/brain/awf185
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion SPET correlated with Braak pathological stage in Alzheimer's disease

Abstract: Reductions in regional cerebral perfusion, particularly in the posterior temporo-parietal lobes, are well recognized in Alzheimer's disease. We set out to correlate perfusion changes, using (99m)Tc-HMPAO single photon emission tomography (SPET), with the pathological stage of Alzheimer's disease. The 'Braak stage' of the distribution of neurofibrillary pathology in post-mortem brains was used to classify SPET scans taken in life from a mixed (dementia and control) elderly population into the entorhinal stage (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
114
1
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(139 citation statements)
references
References 40 publications
14
114
1
6
Order By: Relevance
“…Similar findings have also been reported in mild AD (Johnson et al, 2001). More recently, evidence of early AD pathology in these regions was confirmed among MCI patients who came to autopsy (Bradley et al, 2002;Markesbery et al, 2006;Petersen et al, 2006). The temporoparietal perfusion abnormalities noted in our IQ-MI subjects at baseline suggest that AD pathology may have been present at the time of initial evaluation in normal CDR0 subjects.…”
Section: Dm Rentz Et Alsupporting
confidence: 60%
“…Similar findings have also been reported in mild AD (Johnson et al, 2001). More recently, evidence of early AD pathology in these regions was confirmed among MCI patients who came to autopsy (Bradley et al, 2002;Markesbery et al, 2006;Petersen et al, 2006). The temporoparietal perfusion abnormalities noted in our IQ-MI subjects at baseline suggest that AD pathology may have been present at the time of initial evaluation in normal CDR0 subjects.…”
Section: Dm Rentz Et Alsupporting
confidence: 60%
“…Their contribution to an imaging diagnosis in AD is the pattern of reduction in blood flow or glucose uptake in areas of the brain typically affected by tau aggregation pathology [36]. While both provide indirect measures of normal brain metabolic activity (i.e., oxygen and glucose consumption respectively), their ability to demonstrate deficits due to neuropathology is similar [36,37]. The spatial resolution of PET is higher, but by using voxel-based image analysis methods (as was the case in the present study), both have comparable accuracy [38].…”
Section: Discussionmentioning
confidence: 99%
“…Deficits shown by HMPAO-SPECT in brain regions affected by tau aggregation pathology have been shown to correlate with tau aggregation pathology as measured by Braak stage [36]. The ROI and SPM analyses of rCBF decline provide a mapping of the regions of treatment benefit to those known to be particularly rich in tangles, notably medial temporal lobe structures and temporoparietal regions [39].…”
Section: Discussionmentioning
confidence: 99%
“…Only recently has it been suggested that younger AD patients might also have early synaptic loss in the PCC and precuneus [35] and that there might be precuneus volume loss in younger AD patients [36]. In a study that combined single photon emission CT (SPECT) with post-mortem Braak staging [37], hypometabolism of the precuneus was found in patients who were classified as belonging to either the Braak entorhinal or limbic stage (i.e. mild AD changes).…”
Section: Discussionmentioning
confidence: 99%